Nuclear science and technology in the Malaysian context: Three phases of technoscientific knowledge transfer (ETTLG) - Lee, Clarissa Ai Ling* (Open Access, 2017)
This essay considers the development of the nuclear science programme in Malaysia from a transnational perspective by examining the interactions between state agents and other external nuclear-knowledge/technology related actors and agents. Going beyond the model of knowledge diffusion that brings together concerns articulated in Harris’s (2011) geographies of long distance knowledge and Reinhardt’s (2011) role of the expert in knowledge transfer, the proposed three-phase model of knowledge transfer theorises the pathways undertaken by a late-blooming participant of modern science and technology as the latter moves from epistemic dependency to increasing independence despite the hurdles encountered, and the underdevelopment of many areas of its technoscientific economy. The model considers tensions stemming from the pressures of expediency for meeting national developmental goals on the one side, and the call to support the objectives of basic science on the other. The three phases of the model are epistemic transition, epistemic transplantation and localisation, and epistemic generation (ETTLG). As additional support for the proposed model, three arguments are proffered as deeper explanations of the epistemic goal by using Malaysia as a case study: knowledge transfer for political legitimization, knowledge transfer for countering agnotology, and knowledge transfer for social engineering and science diplomacy.